A study on utilizing different metals as the back contact of CH3NH3PbI3 perovskite solar cells. Issue 35 (16th August 2016) - Behrouznejad, F.; Shahbazi, S.; Taghavinia, N.; Wu, Hui-Ping; Wei-Guang Diau, Eric
Abstract : Ag, Au, Pt prove best metal-contacts for perovskite solar cells. Ag and Cu are chemically unstable. Ni and Cr show low performance. Abstract : Organic–inorganic halide perovskite solar cells have attracted considerable interest due to their high efficiency and low fabrication cost. Au and Ag are usually used as the back contact metals but have limitations such as Au is too expensive and Ag is unstable. Here, Pt, Au, Ni, Cu, Cr and Ag were studied as the back contact electrodes for perovskite solar cells. We looked at how the work function of metals can affect their photovoltaic characteristics. The compositional and electrical characterizations were studied using X-ray photoelectron spectroscopy (XPS) and electrochemical impedance spectroscopy (EIS). The general trend observed was that the shunt resistance and open-circuit voltage of the devices decrease with the decreasing work function of the contact metal. The EIS measurements indicated that the internal resistance of the cell decreases when using spiro-OMeTAD in Au, Ag and Pt devices, whereas in the case of Ni, Cu and Cr devices, the internal resistance of the interface increases, indicating that spiro-OMeTAD is not a good HTM with these metal electrodes. Our results also showed that Cu and Ag were not stable in these devices and that the performance of the Ag device degraded faster than that of the Cu device. Efficiencies of 16.4%, 16.5%, 14.7%, 7.8%, 9.2% and 0.04% were obtained for the devices with Au, Ag, Pt, Ni, Cu and Cr, respectively.